Navigating secure storage requirements for EUDI Wallets: a review paper - Zahra Ebadi Ansaroudi; Giada Sciarretta; Andrea De Maria; Silvio Ranise (EURASIP Journal on Information Security)
Abstract The European Digital Identity Wallet (EUDI Wallet) plays a pivotal role in shaping digital identity across the EU, necessitating a secure storage solution compliant with eIDAS2 regulation. In this study, we first analyze mobile secure storage solutions for the EUDI Wallet, identifying any gaps between current offerings and the EUDI Wallet’s requirements. Our analysis indicates a significant shortfall in the availability of mobile native solutions, with only approximately 10.5% of mobile phones in the Italian market currently adhering to the stringent requirements mandated by eIDAS2. Consequently, we explore and evaluate alternative design solutions in terms of their feasibility and integration potential.